Disseminated Cutaneous Mycobacterium Fortuitum-Chelonae Complex Infection in a Young, Immunocompetent Patient: A Case Report: A Case Report - Rozhan, Atikah; Abdullah, Kahairi; Asha’ari, Zamzil Amin (IIUM Medical Journal Malaysia, 2021)
Mycobacteria fortuitum and chelonae are a group of Rapidly Growing Mycobacteria (RGM) that can cause skin infections, most commonly in immunocompromised patients. RGM can also infect immunocompetent patients, but the disease is usually localized. Immunocompetent patients infected by RGM usually had a predisposing condition leading to the skin infection. We present a case of an immunocompetent patient with no predisposing factors, who presented with a chronic lesion on his neck that disseminated to his axilla. Culture and species identification from the skin biopsy revealed Mycobacterium fortuitum-chelonae complex. The patient was treated with a combination of surgery and multi-drug therapy. This case report highlights the rarity of cutaneous RGM infections encountered in ENT setting and the diagnostic dilemma due to the non-typical characteristics of skin lesion in RGM infections.